CHARACTERISTICS OF NARRATIVE LANGUAGE IN THE HISTORICAL NOVEL NGUYEN DU BY NGUYEN THE QUANG - Nguyễn Thị Thẩm Mỹ (Tạp chí Khoa học Đại học Đà Lạt)
In this article, we introduce some basic language characteristics in Nguyễn Du by Nguyen The Quang: Narrative language, dialogue language, and monologue language. We discuss the ideology and theme of the work as well as contribute to affirming the value of the work in the development of the modern Vietnamese novel, especially historical fiction.